Answer:
g(x) = [tex]x^{2}[/tex] + 4x + 3; x = -3, -1; g(x) = 3
Step-by-step explanation:
a) The standard form of a quadratic function is:
f(x) = a[tex]x^{2}[/tex] + bx + c
Now, replace the variables with the values given.
g(x) = [tex]x^{2}[/tex] + 4x + 3
b) To find the zeros of the function (x-intercepts), set y to 0 and solve for x:
g(x) = [tex]x^{2}[/tex] + 4x + 3
0 = [tex]x^{2}[/tex] + 4x + 3
(x + 3)(x + 1) = 0
(x + 3) = 0
x = -3
(x + 1) = 0
x = -1
c) To find the y-intercept of the function, set the x values to 0:
g(x) = [tex]x^{2}[/tex] + 4x + 3
g(x) = 3